2022
DOI: 10.2196/36696
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Indicators Measured Using Earable Devices: Systematic Review

Abstract: Background Earable devices are novel, wearable Internet of Things devices that are user-friendly and have potential applications in mobile health care. The position of the ear is advantageous for assessing vital status and detecting diseases through reliable and comfortable sensing devices. Objective Our study aimed to review the utility of health-related indicators derived from earable devices and propose an improved definition of disease prevention. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Our findings from a sensor located at ear-level open the door for other application fields in this age range, e.g., IMU integration in in-ear headphones worn during sporting activities ( 29 ). Accuracy and precision for the Audéo sensor, and in general for accelerometers aiming to predict EE in a variety of activities (including ADLs, sporting activities), can be improved by the incorporation of heart rate (HR) data, as evidenced by O’Driscoll et al's ( 6 ) meta-analysis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our findings from a sensor located at ear-level open the door for other application fields in this age range, e.g., IMU integration in in-ear headphones worn during sporting activities ( 29 ). Accuracy and precision for the Audéo sensor, and in general for accelerometers aiming to predict EE in a variety of activities (including ADLs, sporting activities), can be improved by the incorporation of heart rate (HR) data, as evidenced by O’Driscoll et al's ( 6 ) meta-analysis.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies evaluating accelerometers worn around the ear ( 26 28 ) have shown promise in estimating EE but were limited to younger adults and a narrow range of activities, and none incorporated the accelerometer directly into a hearing aid. Addressing this gap and given the rising trend of wearables with health sensors ( 29 ), the current study aimed to explore whether a similar approach can effectively predict EE in a broader spectrum of ADL for middle-aged and older adults, specifically through an accelerometer integrated into a hearing aid. Thus, this research focused on adults aged 45–64 years, and those 65 years and older, comparing the accuracy of this new sensor placement with a research device worn at the hip and wrist, as well as wrist-worn consumer devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ear has been recognized as a prime location to exploit for the purpose of health biometrics [13][14][15][16][17]. Building on that sentiment, the first two challenges outlined above can be addressed by integrating temperature measurement into devices that are already commonly worn by consumers, such as hearing aids and earbuds.…”
mentioning
confidence: 99%